Pemerolehan Bahasa Indonesia Anak Usia 2,5 Tahun Dalam Kajian Fonologi, Morfologi, dan Sintaksis - Fera Zasrianita (Jurnal Hawa : Studi Pengarus Utamaan Gender dan Anak, 2020)
This paper aims to study and describe the language acquisition system from the age of 2 years 3months to the age of 2 years 6 months, specifically covering phonology, morphology, and syntax. The research method used in this study is qualitative method by studying case study. After analyzing the acquisition of language in Syafiq, starting from the acquisition of phonological, morphological, and syntactic obtained: 1. A normal child can be used as phonemes, and limited words according to the environment and the objecs that are around it. Besides that, the words that came out were still fragmented and the words were still slipped. 2. The words produced have started to increase and star from nouns and verbs. The development of the treasury has begun with abstract nouns. While nouns and verbs are also obtained due to the repetition of the acquisition of friends, brothers, or parents. 3. Syafiq was able to compose simple words, ranging from one, two to three words, and finally make sentences. Simple sentences that are spoken are still completed in a simple order and not yet finished. It is also undeniable that a normal child will be able to acquire first language when his nerves and brain tissue are not difficult during his growing period. Psychological and nutritional development also environment plays an important role in children’s motoric growth.